การศึกษาเปรียบเทียบการออกเสียง ความหมาย และชนิดของคำอักษรพ้องรูป “多音字” ในภาษาจีน” - นามวัฒน์ , ธนัชพร (Journal of Human and Society, Sisaket Rajabhat University, 2022)
บทความวิจัยการศึกษาเปรียบเทียบการออกเสียง ความหมาย และชนิดของ คำอักษรพ้องรูป “多音字” ในภาษาจีน มีวัตถุประสงค์เพื่อศึกษาการออกเสียง รูปแบบทางความหมายและชนิดของคำอักษรพ้องรูปในภาษาจีนโดยรวบรวมข้อมูลทั้งหมดจากพจนานุกรมภาษาไทย-จีน จำนวน 564 คำมาวิเคราะห์ พบว่า ส่วนใหญ่ มีคำอักษรพ้องรูปอ่านได้ 2 เสียงมากที่สุด จำนวน 454 คำ คิดเป็นร้อยละ 80.50 คำและคำอักษรพ้องรูปอ่านได้ 6 เสียงน้อยที่สุด จำนวน 1 คำ คิดเป็นร้อยละ 0.18 คำ คำอักษรพ้องรูปมีการอ่านออกเสียงได้หลายเสียงทำให้รูปแบบทางความหมายและชนิดของคำเปลี่ยนแปลงไปจากเดิม ผลการวิจัยนี้สามารถเพิ่มความเข้าใจและลดความสับสนในการใช้คำอักษรพ้องรูปในภาษาจีน และเพื่อเป็นข้อมูลในการศึกษาระบบคำในภาษาจีนในอนาคตต่อไป The purpose of studying of comparison of pronunciation, meaning and parts of speech of homonyms “多音字” in Chinese is to find the pattern of pronounciation, meaning, and the parts of speech of homonyms in Chinese. The research analyzed 564 words in Thai-Chinese dictionary and founded that most of homonyms could be pronounced in two tones of Chinese over 454 words which accounted for 80.50% of words while the least was founded to be six tones which had only one word and constituted 0.18% of words. Homonyms could pronounce in many tones which lead to a mismatch in meaning and parts of speech from the origin. The result of this study will enhance more understanding and reduce the confusion of using Chinese homonyms words. In addition, it could be a data for the future studying of systematic Chinese words.